Mudharabah Hasil Pertanian Di Tinjau Dari Undang Undang Dan Hukum Islam - Jannahar Saddam Ash Shidiqie (Universitas Alma Ata, 2017)
This research aims to analyze the implementation of profit sharing agreement for paddy field in Gamping Sub-district using Law No. 2 of 1960 and Islamic Law. The conclusion of this study are: The implementation of profit sharing agreement for paddy fields in Gamping Sub-district is not fully in accordance with the Law No. 2 of 1960 and the Islamic law. The agreement of profit sharing in Gamping Sub-district in general is conducted orally, based on trust, and without any witnesses. The balance of profit sharing used in general is